Booked on murder : a haunted library mystery - Brook, Allison (Brook, Allison. Haunted library mystery, 2024)
"Carrie Singleton is ready to kiss the single life goodbye. Her wedding to Dylan Avery is just a few weeks away, and a happy ending is about to be hers. But when a body is found on the lawn of their wedding venue, happily-ever-after is looking deadlier than ever. The victim turns out to be Billy Carpenter, a young man recently released from prison after serving time for a bank robbery. The stolen money he'd buried is gone and Carrie and the police suspect Billy's two alleged co-conspirators, his friends Luke Rizzo and Tino Valdez. But then Luke is murdered and Tino is nowhere to be found. With no leads and only a week to go before her big day, Carrie is on the hunt for clues. She hopes to wrap up this investigation with a neat bow before she and Dylan tie the knot. Carrie has something old, something new, and something borrowed ready for her walk down the aisle. Now she needs to find the killer without becoming the 'something blue'"--